A novel autophagy enhancer as a therapeutic agent against metabolic syndrome and diabetes - Hyejin Lim (Nature Portfolio, 2018)
Autophagy plays an important role in metabolic functions and increased autophagic activity may be beneficial for metabolic disorders. Here the authors screen a chemical library for enhancer of autophagic flux and identify small molecules that improve the metabolic profile by increasing lysosomial functions.